(3GdaQb aj GddZIs - (3KGHJ Hf CHj KGHJ SYjO Gdchaj , CHh eMeO,J (B250 (3g` s
(3ChdgG (B:s
(3Chd GdehLhO efg bhd QDHI (B: (3cGdMhJ dGjQhjg TF jdgeg jUHM XeBf hai GdHMQ aeg s
(3BNQgG (B:s
(3BNQ GdehLhO efg ef ChUGa GdeTF (B: (3abGd dg (B: (3hcja YdeJ Pdc ? bGd (B: (3EfgG eTJ acJaJ hNHJ s
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B97 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B100 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B248s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
Keywords: (3GddZIs